Barriers to implementation of innovative writing instruction: A mixed-method examination of collaborative and technology-enhanced approaches in Nigerian secondary schools - Elizabeth Adedokun; Theophilus Adedokun (CV. Yudhistt Fateeh, 2026)
While collaborative, creative and technology-enhanced approaches show strong research support for writing instruction, few studies examine why these approaches remain underutilised in Nigerian secondary schools. This mixed-method study identified teaching practices, their pedagogical value and implementation barriers. A survey of 167 English teachers (103 public, 64 private schools) measured technique frequency using a four-point Likert scale, supplemented by open-ended responses. Quantitative findings revealed collaborative learning (M = 3.22), digital integration (M = 3.19) and text framework support (M = 3.37) were used significantly less than traditional teacher-directed methods (M = 3.60). Digital tools showed the widest variation (SD = 0.87), indicating inconsistent adoption. Qualitative analysis revealed that teachers implementing these approaches reported substantial benefits for student engagement and writing quality. However, four barriers constrained wider adoption: large class sizes, insufficient technology infrastructure, limited training in contemporary pedagogies, and examination pressures. Culturally sustaining resources, including Nigerian folktales and authentic texts, significantly enhanced engagement. The study reveals a critical paradox: innovative approaches yield pedagogical benefits when implemented, yet systemic constraints prevent widespread use. Findings inform professional development and policy initiatives to expand teachers' instructional capacity and enhance English language education in Nigerian secondary schools.